Thermal transmittance of lightweight steel framed walls: Experimental versus numerical and analytical approaches - Santos, Paulo (2019)
Given the great influence of the thermal transmittance of the building envelope on the overall thermal performance and energy efficiency of the building, it is essential to accurately determine the U-value of the main building envelope elements. Due to the great heterogeneity of the thermal conductivity of the elements presented in a lightweight steel-framed (LSF) wall, and to the geometric complexity of some steel framed structures, a reliable estimation of the thermal transmittance of LSF elements is even more challenging. Indeed, thermal bridging originated by steel studs must be considered in the assessment of the thermal transmittance of LSF walls. In this work, the thermal transmittance (U-value) of three LSF walls with different configurations will be investigated based on four different approaches: experimental laboratorial measurements based on the Heat Flow Meter (HFM) method; 3D finite element method (FEM) simulations using ANSYS CFX® software; 2D FEM-based simulations using THERM software; analytical estimations based on the ISO 6946 procedure for building components with inhomogeneous layers. Several verification procedures were performed to ensure the reliability of the results. It was found that a secondary wood stud can mitigate the thermal bridging effect of the steel frame and improve the LSF thermal performance, which is more noticeable when there is no thermal insulation. Furthermore, a good agreement was found between the results of the 2D FEM and the analytical ISO 6946 approaches for the LSF wall with only vertical steel studs.